ATHLETES BODY IMAGE PERCEPTION (Fiep Bulletin - online, 2013)
Social pressures and/or the search for a better physical performance in sports may cause the dissatisfaction with body image (BI). In some sports where the beauty, the lightness or a low body weight may contribute to the best performance, the perception of the BI can be change. The main of this study is analyzing the athletes' BI satisfaction. Seventeen women sailors were evaluated (18.3 ±7.4 years) and 12 young non-athletes (19.50 ±1.78 years). The degree of dissatisfaction with the BI was obtained by the Body Shape Questionnaire (BSQ). It is a version translated and validated to Portuguese. The athletes showed similar results (p>0.05) to the non-athletes for age, body weight, height and body fat (%BF). The correlation between the result of BSQ and %BF was positive (athletes=0.65 ; non-athletes=0.58). These study verified that 36% of the athletes have some level of dissatisfaction with the BI, but they had pattern of %BF within health limits set for age and gender.
Keywords: Body image; body fat and athletes